“Cesta entomológica artesanal” um recurso didático para facilitar no processo ensino – aprendizagem de ciências na Escola Afro Amazônida, Quilombo Murumuru, Santarém - PA. - MOTA, Cláudia Bentes (Universidade Federal do Oeste do Pará, 2024)
Over the years, science teaching has dedicated time and attention to studies related to the teaching-learning process, as many students have difficulty with some contents in this area of knowledge. In this context, the content of the Insecta class is also inserted, which is still seen in the classrooms in a negative way about human life, a reason that may be related to the fact that they are unable to relate what is learned at school with everyday life. Therefore, the objective of this work was to elaborate a didactic resource in order to facilitate the assimilation of the content of this class, in order to reduce the existing barriers that hinder the teachinglearning process of science in the Afro Amazonian school, Quilombo Murumuru, Santarém - PA. In view of this, the didactic material was made in the form of a “handmade entomological basket” from natural resources extracted from the quilombola community in which the research was carried out, as well as straw and thorns from the tucumanzeiro palm. Such structuring aimed to provide students and teachers with pedagogical material focused on the local reality in which the school is inserted. The research was of a qualitative-quantitative nature applied to a regular class of the 7th grade of elementary school. Data were collected through two questionnaires applied to the students, as well as to the subject's teacher, and analyzed in a comparative way through graphs and groups in tables. The resource proved to be effective for science teaching so that it was verified after the data analysis that the assimilation of the content referring to the external morphology of the Insecta class was successful after the intervention of the activity using the "Entomological Basket". In addition, its use proved to be viable in the perception of the questioned teacher, especially in relation to making with local faunal resources, as well as floristic. In view of this, the didactic material entitled “Handmade Entomological Basket” is an alternative for teaching and learning science in the quilombola school.